Effects of fodder production on smallholder farmers’ household income in Homa Bay County, Kenya: An application of propensity score matching - Mary Stacey Ayuko; Job Kibiwot Lagat; Michael Hauser; Kevin Okoth Ouko; Dick Chune Midamba (Cogent Food & Agriculture, 2024)
The global feed production has increased in the past few years. Despite the growing trend, the current production does not meet the demand in Kenya. The government of Kenya has initiated several efforts towards promoting fodder production to increase milk production and household income. This study analysed the effects of fodder production on household income in Homa Bay County, Kenya using the Propensity Score Matching (PSM) technique. The study used primary data collected through structured questionnaires in Homabay County, Kenya from a sample size of 300 smallholder farmers. Results indicated that years of schooling, herd size, household size, labour used in land preparation, and land size under fodder had a positive influence on the probability of farmers to mainly feed their livestock on Napier grass. On the contrary, the number of extension contacts negatively influenced the probability of farmers feeding their livestock on Napier grass. Results show that there was a significant difference between the incomes of farmers who fed their cattle on Napier grass and those who mainly grazed their cattle on natural grass. Specifically, smallholder farmers who fed their livestock on Napier grass reported a Kshs. 3,916.67 (USD 25.71) higher income than their counterparts who grazed their livestock on natural grass reflecting an increase by 24.94%. Thus, the study recommends the need for both the national and county governments to incorporate fodder production as a key area for livestock development agenda in their policy plans to improve the farmers’ income.